Understanding Flipped Classroom in the EFL Context: A Gender-Based Perspective - Alghamdi, Farah Rashed; Almalki, Mansoor S. (Advances in Social Sciences Research Journal, 2022)
This study aims to investigate students’ perspectives towards flipped classrooms (FCs) while determining their preferences and suggestions for better FC practices. All participants were required to watch videos before the lectures and to practice the content within the class. Both qualitative and quantitative methods were used, and data were gathered through a survey and semi-structured interviews. The participants were in their first and second years. The results illustrated that both genders indicated positive perceptions towards FCs, with females reacting more positively than males. The FC model was preferred over the traditional classroom due to its enhancement of engagement and motivation, with males showing high satisfaction with technology out-of-class, indicating that it reinforced self-learning performance. Most male participants reported that they preferred instructor explanations over videos. Both genders recommended having different materials alongside video lectures that were short and supplemented with pictures to increase engagement. Considering the findings, practical implications were recommended.